Demographic Variables as Predictors of Psychological Well-Being Among Nurses in Public Hospitals in Benue State, Nigeria - Alhassan, Okpoju Daniel; Zakariah, Danladi; Ibrahim, Mboma (Darul Yasin Al Sys, 2025)
This study investigated demographic variables as predictors of psychological wellbeing among nurses in public hospitals in Benue State, Nigeria. A total of 286 nurses participated, comprising 122 males (42.7%) and 164 females (57.3%), with a mean age of 44.4 years. Using a cross-sectional survey design, participants were drawn from nine public hospitals across three geopolitical zones through cluster and purposive sampling techniques, from a total nurse population of 1,120. Data were collected using the standardized Carol Ryff Psychological Wellbeing Scale, and hypotheses were tested across six wellbeing dimensions at a 0.05 significance level using multivariate analysis of variance. The first hypothesis predicted a significant effect of age on psychological wellbeing; however, results showed no significant influence of age on overall wellbeing [R = .101, R² = .010, F(1,263) = 2.867, p > .05], nor on any of its dimensions, including autonomy, environmental mastery, positive relations, purpose in life, and self-acceptance. The second hypothesis posited that sex, cadre, marital status, and duration of service would have significant main and interaction effects on wellbeing. Findings revealed significant effects only for duration of service on personal growth [F(3) = 2.931, p < .01], marital status on overall wellbeing [F(1) = 6.386, p < .01], and marital status on positive relations [F(1) = 30.053, p < .05]. Thus, duration of service and marital status emerged as significant predictors, partially confirming the hypothesis. The study recommends that government employ clinical psychologists in public hospitals to periodically assess, diagnose, and manage psychological issues among nurses, as well as provide training on social and occupational norms to improve wellbeing and optimize professional functioning.